Function, gene organization and protein structures of 11beta-hydroxysteroid dehydrogenase isoforms. - Oppermann, U; Persson, B; Jörnvall, H (1997)
Enzymatic interconversion of active and inactive glucocorticoid hormone is important, and is carried out physiologically by 11beta-hydroxysteroid dehydrogenase (11beta-HSD) isoforms, explaining their role in cellular and toxicological processes. Two forms of the enzyme, 11beta-HSD-1 and 11beta-HSD-2, belonging to the protein superfamily of short-chain dehydrogenases/reductases, have been structurally and functionally characterised. Although displaying dehydrogenase and reductase activities in vitro, the dominant in vivo function of the type-1 enzyme might be to work as a reductase, thus generating active cortisol from inactive cortisone precursors. On the other hand, for adrenal glucocorticoids the type-2 enzyme seems to be exclusively a dehydrogenase and, by inactivating glucocorticoids, confers specificity to peripheral mineralocorticoid receptors.